2020
DOI: 10.1108/jeee-07-2020-0235
|View full text |Cite
|
Sign up to set email alerts
|

From entrepreneurial intention to enterprise creation: the case of Estonia

Abstract: Purpose The present paper aims to identify a set of cognitive and contextual characteristics that explain entrepreneurial intentions, actions and venture creation, thereby covering three successive stages of becoming an entrepreneur. Design/methodology/approach The analysis is based on entrepreneurship data from a self-reported online survey (n = 1,492) gathered among the Estonian population in 2017. The authors use an exploratory factor analysis to reduce initial survey responses about the external environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Future research can also consider the influence of additional personal traits and skills such as entrepreneurial passion, creativity, interpersonal relationship abilities, and analytical and logical skills on entrepreneurial intent (Cristina, 2016). Comparing how individual traits and entrepreneurial skills differ across groups with different profiles (e.g., gender, age, and employment status) is another relevant extension to the present research (Kallas and Parts, 2020;Saral and Alpkan, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Future research can also consider the influence of additional personal traits and skills such as entrepreneurial passion, creativity, interpersonal relationship abilities, and analytical and logical skills on entrepreneurial intent (Cristina, 2016). Comparing how individual traits and entrepreneurial skills differ across groups with different profiles (e.g., gender, age, and employment status) is another relevant extension to the present research (Kallas and Parts, 2020;Saral and Alpkan, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…In this context, Kallas & Parts (2020) found that regarding differences between entrepreneurs and nonentrepreneurs, entrepreneurs have a more positive perception of the business environment and the ease of doing business, including the simplicity of entrepreneurship-related legislation. On the other hand, entrepreneurs are more skeptical about the availability of financial resources, and they perceive public attitudes and the role of entrepreneurs in a society less positively.…”
Section: Literature Beckgroundmentioning
confidence: 99%
“…Many studies showed that developing positive attitudes towards entrepreneurship is relevant factor in all stages of becoming an entrepreneur (e.g. Anor Salim et al, 2019;Yousaf et al, 2021;Kallas & Parts, 2020). Financing opportunities both from private and public institutions and keeping entrepreneurship legislation simple and transparent have the utmost importance in increasing the share of entrepreneurs and entrepreneurship-related benefits in society (Kallas & Parts, 2020).…”
Section: Literature Beckgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies state that the role of communication or familiarity has a very large role to play in increasing the acceptance of individuals regarding new policies related to vehicles or modes of transportation (Mamat, 2014;Wahab, 2014;Mamat, 2015). However, this concept of communication and civility is very broad and focuses on the individual's perception of the policy and not the knowledge of the policy itself (Chan, 2018;Kallas and Parts, 2021). Until now, there has still been little research that directly reveals the relationship between knowledge and an individual's readiness to accept new policies.…”
Section: The Impact Of Knowledge and Readinessmentioning
confidence: 99%